Sejarah Panjang Korupsi di Indonesia dan Upaya Pemberantasannya - Suraji Suraji (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2008)
One of national problem which has not been overcome is corruption. This is also including the eradication effort. Corruption involves both public and private institutions. In institution of state can be witnessed corruption happened is good instituted executive, legislative, and judicative. Public institution is the institution whch is giving public service, law and interest aggregation which is the existing increasingly real where elite region becomes corruption arena. But if the institution exactly becomes as result of to its the power doesn't work carefully and is not believe by public of course become dilemma to the future of and state progress. in power and political context, corruption follows opinion Lord Acton that is assumed power product, through power tends to corrupt, absolute of power corrupts absolutely. From the aspect of this approach corruption happened in Indonesia not quit of power and or power heritage product from regime to regime that is not finalized carefully. Mean finite old order regime of reform had endowed its (the corruption and eradication) only mere rethoric. Mean has not made political will in eradication of corruption. So very fair if the existing of rampant corruption and has been believed as culture for public Indonesia. Efforts which have been done at reform era as democracy era claiming change and freedom of enough realities even has not is optimal result of his. This thing is required by hardwork for all element of nation to coalesce jihad fight against corruption.